How Trustworthy is Light Transmittance Platelet Aggregometry With Low Platelet Count Samples? Insights From Test Replicates and Retrospective Analysis of Several Decades of Diagnostic Samples - Hayward, Catherine P. M.; Al Dawood, Rabab; Wice, Lindsay; Moffat, Karen A. (International journal of laboratory hematology, 2025)
Light transmission platelet aggregometry (LTA) is useful to diagnose platelet function disorders (PFD). We evaluated the precision and reproducibility of LTA with low platelet count platelet-rich plasma (LPRP). LPRP maximal aggregation (MA) precision for informative agonists and LTA reproducibility were assessed using multiple replicates for adjusted control LPRP (CLPRP) and retrospective analysis of several decades of consecutive patient LPRP (PLPRP) and CLPRP tests with replicates between and/or within tests. Intra-subject CLPRP had acceptable MA CVs and tracings unless platelets were ≤ 25 × 10 /L. Among tests with replicates, PLPRP with ≤ 25 × 10 platelets/L were uncommon (6/247 samples) and 5/6 showed pathognomonic Bernard-Soulier syndrome (BSS) findings. Among evaluated patients (n = 195; diverse diagnoses), 44.6% had abnormal LTA findings on ≥ 1 tests after excluding single, within-test MA outliers in 21/194 PLPRP and 2/27 CLPRP tests. Median, intra-subject, within-test coefficients of variation (CVs) for PLPRP and CLPRP MA responses to informative agonists were acceptable for most agonists, with higher CV for 0.5 mg/mL ristocetin, weak agonists, and impaired responses, and only small differences between MA estimates across agonists. Between-test agreement was good for MA responses, with 80.5% of patients and 98.1% of controls having consistent overall LTA findings, with significantly more patients than controls having consistently abnormal LTA findings (46.3% vs. 0%; p < 0.001). Diagnostic LTA with LPRP has acceptable precision and reproducibility when evaluated with informative agonists. Nonetheless, caution is warranted when testing samples with ≤ 25 × 10 platelets/L, which often show BSS findings.